Penyuluhan Pengelolaan Stress pada Lansia di Rumah Lansia Bahagia Bintan - Handayani, Wulan; Agustina, Puti; Lisandari, Yani; Kurniawan, Rizki (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Stress is an unavoidable reality of everyday life, caused by changes that require adjustment. After being given counseling, it is hoped that the elderly can understand stress management. After getting an explanation about stress management, participants Counselors are expected to know the meaning of stress, the signs and symptoms of stress, the causes of stress, and stress management. The problem is that some elderly people in Bintan Happy House experience mild stress because they still do not understand how to manage stress in the elderly. The basic thing that is offered to help solve the problem is counseling activities for the elderly at Bintan Happy House, which are packaged with the activity name